Profil Kadar Hemoglobin pada Remaja Putri di Wilayah Kepulauan Mentawai: Studi di Kecamatan Sikakap - Mardiani Bebasari; Faridah BD; Lita Angelina Saputri; Iin Prima Fitriah Fitriah; Rati Purnama Sari; Nurul Aziza Ath Thaariq; Wulandari Defera; Yussie Ater Merry; Yuanita Sandra (Jurnal Kebidanan Besurek, 2026)
Anemia is a significant global public health challenge, particularly among adolescent girls due to rapid growth phases and menstrual cycles. This study aims to identify the hemoglobin profile and anemia status of adolescent girls at MTsN 2 Kepulauan Mentawai to provide a foundation for nutritional intervention strategies in island regions. This descriptive study involved 50 female students who had reached menarche. Primary data were collected in April 2025 through digital hemoglobin testing and Mid-Upper Arm Circumference (MUAC) measurements. The results showed that the average age of respondents was 13.8 years, with an average menarche age of 12 years. The participants' average hemoglobin level was 13.9 g/dL; however, an anemia prevalence of 18% (9 individuals) was identified, with values ranging from 10 g/dL to 16 g/dL. In conclusion, while the group's average hemoglobin level is categorized as normal, a significant portion of adolescent girls still experience anemia. It is essential to strengthen intervention programs through balanced nutrition education using local food sources and improving compliance with Iron Supplementation Tablets (TTD) to enhance the iron reserves of students in the region.